The support features for the intelligent terminal emulator; Building a network adapter card for IBM working in a ring topology local area network Part II; Building a standard central controller for local area network using star topology; Pengkod dan penyahkod DTMF Bahagian I (Perisian); Screen transferring and massege switching across a network; A point to point computer communication link using communication controller chip; Bit error rate measurement for high data transmission; Pemproses enkripsi piawai (Bahagian 3) : implementasi DES dengan perisian [mikrofilem] - Fauziah Hanim Omar; Jasmi Mohd Daron; Jayaseelan Manickam; Mohd. Zaki Yahaya; Ooi, Foong Yen; Tee, Tah Wee; Thomas Cheriyan; Voo, Fui Ken (Sekudai : UTM, 1992)
Project paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 1992